Perceived values of modern mathematics of selected teachers in the Division Occidental Mindoro - Masangkay, Nicolas Villamar 1924- ([s.n.], 1973)
A tool to get the teacher respondents' perception of teaching Modern Mathematics was constructed in this study. It was validated by a group of selected teachers in the same division.